Artificial Intelligence and Makassar Oral Literature: Transforming “Sinrilik Bosi Timurung” for Sustainable Education - Abd. Rahim; Andi Fatimah Yunus; Nursalam Nursalam; Ridwan Ridwan; Nurhikmah Nurhikmah (Jurnal Pendidikan Terapan, 2026)
In the era of globalization, the existence of oral literature as an intangible cultural heritage is facing the threat of extinction due to the lack of intergenerational transmission and adaptive documentation aligned with contemporary developments. Limited mastery of regional languages has also become a major obstacle in understanding Makassarese oral literature. This study aims to explore the potential implementation of Artificial Intelligence (AI) in transforming the Makassarese oral literature Sinrilik Bosi Timurung (SBT) into an interactive digital format as an effort to preserve intangible cultural heritage through sustainable education. The study employed a descriptive qualitative method with a case study approach, integrating traditional documentation techniques with Natural Language Processing (NLP) technology and AI-based generative media. The findings indicate that AI-based digital transformation can bridge language and accessibility barriers through contextual automatic translation and more engaging visualization of oral narratives for students. The integration of SBT into the 2025 curriculum primarily contributes to improving learning quality, enhancing critical thinking skills, and introducing coding and Artificial Intelligence (AI) to support Education for Sustainable Development (ESD). Furthermore, the incorporation of SBT oral literature into the framework of sustainable education promotes socio-cultural awareness, particularly in fostering understanding and tolerance toward cultural diversity. The local wisdom values embedded in the story include historical awareness, honesty, religiosity, mutual cooperation, morality, loyalty, and family values. Each stanza of SBT serves not merely as entertainment, but also as an educational medium that conveys noble values. SBT storytellers hold an essential role as custodians of cultural values and history. Therefore, the synergy between AI technology and local wisdom represents a crucial strategy for ensuring the sustainability of cultural identity amid the currents of modernization.